Differential expression of a subset of ribosomal protein genes in cell lines derived from human nasopharyngeal epithelium - Sim, E.U.H.; Ang, C.H.; Ng, C.C.; Lee, C.W.; Narayanan, K. (Nature Publishing Group, 2010)
Extraribosomal functions of human ribosomal proteins (RPs) include the regulation of cellular growth and differentiation, and are inferred from studies that linked congenital disorders and cancer to the deregulated expression of RP genes. We have previously shown the upregulation and downregulation of RP genes in tumors of colorectal and nasopharyngeal carcinomas (NPCs), respectively. Herein, we show that a subset of RP genes for the large ribosomal subunit is differentially expressed among cell lines derived from the human nasopharyngeal epithelium. Three such genes (RPL27, RPL37a and RPL41) were found to be significantly downregulated in all cell lines derived from NPC tissues compared with a nonmalignant nasopharyngeal epithelial cell line. The expression of RPL37a and RPL41 genes in human nasopharyngeal tissues has not been reported previously. Our findings support earlier suspicions on the existence of NPC-associated RP genes, and indicate their importance in human nasopharyngeal organogenesis. Journal of Human Genetics (2010) 55, 118-120; doi: 10.1038/jhg.2009.124; published online 20 November 2009